Platforms and Palimpsests - Ali Fard (Footprint)
Data platforms increasingly mediate the relationship of society to the data it produces and therefore form a critical layer of the contemporary link between data and urbanisation. However, the current discussion of the impact of data platforms on urbanisation is limited on one hand by an overly metaphoric articulation of platforms, which obscures the material geographies and infrastructural landscapes of data production; and on the other hand, by an administratively bounded reading of platforms, which confines the discussion to only their most visible impact in cities. In this article I argue that to fully capture the impact of platforms on urbanisation we need to overcome these limitations by examining the ‘operational landscapes’ of data production and circulation. This extended ontology of platforms positions the spatial discourse of technology in relationship with other forms of capitalist spatial production and opens up the material geographies and infrastructural landscapes of data production for critical engagement as integral parts of the sociotechnical construction of platforms. By examining the data landscapes of Northern Virginia, I illustrate how historic and contemporary forces, actor networks, and urban dynamics contribute to the construction and maintenance of the extended geography of data platforms.